Emphasizing Ethnocentrism and Nation. Reflection on Blocking Factors the Birth of the African Subject - Anselme, Mbemba-Mpandzou (New Horizons in Education and Social Studies Vol. 8, 2021)
The article questions the concepts of ethnocentrism and nation in order to identify the universes of meaning that they contain and assess their relevance in the construction of the nation. From the perspective of this construction, obstacles strew this course and prevent the birth of the African subject, the very one who is the key. The purpose of the article is to give the necessary tools to hatch a national conscience, pledge of strengthening of patriotic bond and citizen. In the current configurations of African “states”, one cannot build the Nation without the contribution of all ethnic identities. And if “to open a school is to close a prison” as Victor Hugo has well pointed out, the school must so be the crucible from which the so-called change of mentality will start, a thorough overhaul both of the institutions of the republic and educational programs that must take into account the realities of Africa and adapt to the challenges of the world today. Without this national consciousness, it is impossible for the young African republics to become nations and to embark on the path of emergence.